2023
DOI: 10.1002/ejic.202300073
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Molybdenum Bimetallic Nitrides as Efficient Catalysts for the Hydrodeoxygenation of Methyl Palmitate

Abstract: Highly efficient catalysts play an important role in the effective use of biomass oil to produce clean fuel. In this work, pure‐phase Ni−Mo bimetallic nitrides (Ni2Mo3N and Ni3Mo3N) with different stoichiometric ratios are prepared by temperature‐programmed nitridation of the metal oxide precursors in ammonia, which are investigated in the hydrodeoxygenation of methyl palmitate in the fixed‐bed reactor at moderate conditions. The physical and chemical properties of catalysts were evaluated by H2‐TPR, XRD, SEM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…The authors suggested that the use of the pyrolysis synthesis technique to form a nitrogenated nickel complex, which provided the N source, followed by a H 2 reduction treatment, which led to metallic Ni and Mo formation, ultimately resulted in a more uniform distribution of N in the lattice compared with other synthesis techniques based on oxide precursors. Similar bimetallic nitride effects have been shown by using Co 3 Mo 3 N, 98 Ni 2 Mo 3 N and Ni 3 Mo 3 N, 99 and Ni–Mo carbonitride 100 for the hydrodeoxygenation and selective bond scission of another fatty ester, methyl palmitate. In particular, the use of Ni–Mo carbonitride (Ni x MoCN) for hydrodeoxygenation and decarbonylation of methyl palmitate represents another promising application of bimetallic TMNs.…”
Section: Case Studies Of Tmn-based Catalystssupporting
confidence: 67%
“…The authors suggested that the use of the pyrolysis synthesis technique to form a nitrogenated nickel complex, which provided the N source, followed by a H 2 reduction treatment, which led to metallic Ni and Mo formation, ultimately resulted in a more uniform distribution of N in the lattice compared with other synthesis techniques based on oxide precursors. Similar bimetallic nitride effects have been shown by using Co 3 Mo 3 N, 98 Ni 2 Mo 3 N and Ni 3 Mo 3 N, 99 and Ni–Mo carbonitride 100 for the hydrodeoxygenation and selective bond scission of another fatty ester, methyl palmitate. In particular, the use of Ni–Mo carbonitride (Ni x MoCN) for hydrodeoxygenation and decarbonylation of methyl palmitate represents another promising application of bimetallic TMNs.…”
Section: Case Studies Of Tmn-based Catalystssupporting
confidence: 67%